2011
DOI: 10.1213/ane.0b013e31822649d4
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Anesthesia on Glycine Absorption in Operative Hysteroscopy

Abstract: Compared with general anesthesia, local anesthesia with sedation is associated with less glycine absorption and should be considered the preferred method of anesthesia for operative hysteroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…In the current case, the patient was under general anesthesia, which delayed the diagnosis. Regional anesthesia may be safer and beneficial to detect the early warning symptoms of this syndrome, since patients are awake (8). General anesthesia with endotracheal intubation could be safer in longer surgeries in which the risks of developing OHIA are high.…”
Section: Discussionmentioning
confidence: 99%
“…In the current case, the patient was under general anesthesia, which delayed the diagnosis. Regional anesthesia may be safer and beneficial to detect the early warning symptoms of this syndrome, since patients are awake (8). General anesthesia with endotracheal intubation could be safer in longer surgeries in which the risks of developing OHIA are high.…”
Section: Discussionmentioning
confidence: 99%
“…This is warranted because a high degree of hemodilution can cause greater coagulation impairment. It has previously been shown that during TURP, irrigation fluid is absorbed at a rate of 10 to 30 ml/min, and the average volume absorbed is 400–700 ml during hysteroscopic transcervical resection of the endometrium (TCRE) [8,21,22]. In the present study, although hypocoagulable change was observed in the 20% hemodilution group, each value of ROTEM parameter was within the normal reference range.…”
Section: Discussionsupporting
confidence: 37%
“…In a RCT [63] comparing type of anaesthesia, women who underwent operative hysteroscopic procedures (endometrial resection with or without polypectomy or myomectomy) under general anaesthesia had a higher median glycine absorption compared to women who underwent these procedures using local paracervical anaesthesia with 1 % lidocaine and midazolam, sufentanil and propofol sedation (480 mL [76–1300 mL] versus 253 mL [70–728 mL], p  = 0.01). General anaesthesia was also associated with a higher rate of glycine absorption >1000 mL (20 % versus 4 %), a greater fall in serum sodium concentration (2.0 meq/L versus 0.5 meq/L and a greater rate of fall in sodium concentration ≥10 meq/L (8 % versus 0 %) than local anaesthesia with sedation.…”
Section: Anaesthesia and Impact Upon Fluid Overload And Electrolyte Imentioning
confidence: 99%